Involving Children and Young People in Health and Social Care Research. - Fleming, Jennie; Boeck, Thilo (Taylor and Francis, 2012)
Led by both children's rights perspectives and methodological arguments, there is an increasing emphasis on children and young people's participation in health and social care research by researchers, policy makers and funding bodies - with many now considering the active involvement of children and young people a requirement.